Incidence and prevalence of ulcerative colitis in Punjab, North India. Issue 11 (21st October 2003) - Sood, A; Midha, V; Sood, N; Bhatia, A S; Avasthi, G
Abstract : Introduction: Ulcerative colitis occurs worldwide. It is considered common in most of Europe and North America and uncommon in most of the developing Asian countries. The incidence/prevalence of ulcerative colitis varies not only according to geographical region but also with race and ethnicity. There are no reported data from India on the incidence of the disease and its prevalence. Material and methods: A house to house survey was conducted by questionnaire, formulated to enquire about symptoms that are suggestive of ulcerative colitis. Those with prolonged diarrhoea with or without rectal bleeding were considered as suspected cases. These suspected cases were subjected to video sigmoidoscopy/colonoscopy and rectal biopsy. In addition, patients already diagnosed and receiving treatment for ulcerative colitis, encountered during the survey, were reviewed. Resurvey of the same areas was conducted after a one year interval to detect new cases. Using direct methods, standardised rates were calculated using world standard population weights 22, 18, 16, 12, 12, 9, 7, 3, and 1 for each 10 year age group. Standardised rates were also obtained separately for males, females, and combined populations, using the Punjab state 1991 population census data. Rates were also estimated according to UK 2000 population data. Ninety five per cent confidence intervals (95% CI) of prevalence and incidence rates of ulcerative colitis were estimated under the assumption that the distribution of cases followed a Poisson probability model. Results: A total population of 51 910 were screened from January to March 1999. We identified 147 suspected cases and of these 23 were finally established as ulcerative colitis cases, giving a crude prevalence rate of 44.3 per 100 000 inhabitants (95% CI 29.4–66.6). A second visit to the same areas after one year identified 10 suspected cases in a population of 49 834. Of these, three were confirmed as "definite" ulcerative colitis giving a crude incidence rate of 6.02 cases per 100 000 inhabitants (95% CI 1.2–17.6). Conclusions: This is the first population based study from India reporting on the incidence and prevalence of ulcerative colitis. The disease frequency is not much less than that reported from Europe and North America.